Transfer as a reciprocal process: How to foster receptivity to results of transdisciplinary research. Issue 104 (February 2020) - Nagy, Emilia; Ransiek, Anna; Schäfer, Martina; Lux, Alexandra; Bergmann, Matthias; Jahn, Thomas; Marg, Oskar; Theiler, Lena
Highlights: Transfer to other contexts is usually an objective of transdisciplinary research to provide sustainability transformations. Transfer is a complex process in which different types of knowledge are mediated to other contexts in various ways. Actors in pick-up contexts also bear responsibility for successful transfer and appropriation. Transfer to other contexts can be steered only to a limited extent, but it can be approached systematically. Generating transfer potential for knowledge and result depends on being aware of potential pick-up contexts. Abstract: Transdisciplinary research (TDR) seeks to address real-world problems and aims to be socially transformative. This normative objective extends beyond particular TDR projects, as real-world problems are embedded in concrete contexts but, at the same time, are also related to wider societal challenges that are not restricted to one context. Therefore, TDR generally entails transfer of knowledge and results to other contexts. However, the TDR discourse has mainly treated transfer efforts from the perspective of scientific generalization, translation and packaging of knowledge. Within this understanding of transfer, little attention has been paid to interplay between contexts and the role of new contexts themselves. This article is based on qualitative explorative research on four TDR projects. Its results were iteratively derived through project analysis, reflection on insights from the literature and discussions with TDR experts. We propose that transfer is a complex reciprocal process in which different types of knowledge are provided and transferred to other contexts, where knowledge is adapted, enriched and modified. In addition to project researchers, actors in other (pick-up) contexts also play an important role for successful transfer and appropriation of TDR results. Generating transfer potential within the duration of a project depends on being aware of potential pick-up contexts. To address the interdependent aspects of transfer (results, mediation, and appropriation in other contexts), we present a comprehensive model outlining TDR transfer processes. To support projects seeking to raise their transfer potential in a more conscious manner, we also formulate three overarching recommendations: 1) process results for transfer adequately, 2) identify and support intermediaries and, 3) increase awareness of and address other contexts. Considering these recommendations while also being aware of their interdependence may increase potential for transfer of knowledge and results to other contexts. Our conceptual understanding acknowledges the complexity and non-linearity of endeavors to take advantage of case-specifically gained knowledge and results in other contexts or at other scales.